Giant Colonic Diverticulum a Rare Complication of a Common Disease - Marques,Isabel (2022)
Abstract An 80-year-old patient presented to the emergency room with a bowel obstruction and a tender epigastric mass. An abdominal computed tomography (CT) described a closed loop small bowel obstruction. An exploratory laparotomy revealed a giant sigmoid diverticulum, of 11cm in diameter, which was resected. The specimen was a true McNutt's type III diverticulum. The patient was discharged after a normal postoperative period and did not suffer any recurrence during a follow-up of more than 6 months. This is a rare complication of a common disease with non-specific presentation and not always accurately described by CT scan. Apart from intestinal volvulus, differential diagnoses include duplication cyst, a giant Meckel’s or duodenal diverticulum, pancreatic pseudocyst and pneumatosis cystoides intestinalis. Surgical resection is the recommended treatment to avoid perforation and peritonitis. Diverticulectomy is a safe option for a patient with acute presentation in the emergency room.